THEORY OF GARDNER 'ARTISTIC SYMBOL' : AN ANALYTICAL STUDY - Rajput, Pratibha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper study art as in form of symbols and do analytical study the theory of Harvard Gardner 'artistic symbols' presented in child art and symbols used in different artist's paintings. In modern art there are many theories on art appreciation and Gardner theory of artistic symbol is one of them. Gardner developed his theory on the basis of American philosopher Nelson Goodman's theory of symbols. In 1973-1980 Gardner experiment about the stages of child brain development and study about children's creative expression and used symbols by them. Also study the symbols used by different artists in their paintings.